Clinical Experience with Regenerative Therapy in Heart Failure: Advancing Care with Cardiopoietic Stem Cell Interventions - Bartunek, Jozef (Circ Res, 2018)
Adoption of regenerative strategies for heart failure is challenged by mixed outcomes in clinical trials. Ongoing development plans strive to improve biotherapeutic potency, optimize delivery, standardize dosing, and target responsive patient populations. The Congestive Heart Failure Cardiopoietic Regenerative Therapy (CHART) program offers advanced experience in clinical development of next generation regenerative therapies.